2019
DOI: 10.1186/s40425-019-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient identification of neoantigen-specific T-cell responses in advanced human ovarian cancer

Abstract: Background Efficient identification of neoantigen-specific T-cell responses in epithelial ovarian cancer (EOC) remains a challenge. Existing investigations of spontaneous T-cell response to tumor neoepitope in EOC have taken the approach of comprehensive screening all neoantigen candidates, with a validation rate of 0.5–2%. Methods Whole-exome and transcriptome sequencing analysis of treatment-naive EOC patients were performed to identify neoantigen candidates, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 89 publications
(102 reference statements)
2
55
0
Order By: Relevance
“…After the incorporation of tumor infiltrating lymphocytes (TILs) containing~25% neoantigen-specific auxiliary Th1 cells into tumor tissues, the target lesions of the patients reduced, and the stable time of the disease was prolonged, leading to significant tumor regression. In the current study, Song et al [128] sequenced whole exome and transcriptomes in patients with epithelial ovarian cancer (EOC) to identify neoantigen candidates and then analyzed the reactions of neoantigen-specific CD4+ and CD8+ T cell response in tumor or the peripheral blood. The specific T cell receptors (TCR) were transferred to peripheral blood T cells, making them with a neoantigen reactivity.…”
Section: Combination Of Neoantigen Vaccine With Other Therapiesmentioning
confidence: 99%
“…After the incorporation of tumor infiltrating lymphocytes (TILs) containing~25% neoantigen-specific auxiliary Th1 cells into tumor tissues, the target lesions of the patients reduced, and the stable time of the disease was prolonged, leading to significant tumor regression. In the current study, Song et al [128] sequenced whole exome and transcriptomes in patients with epithelial ovarian cancer (EOC) to identify neoantigen candidates and then analyzed the reactions of neoantigen-specific CD4+ and CD8+ T cell response in tumor or the peripheral blood. The specific T cell receptors (TCR) were transferred to peripheral blood T cells, making them with a neoantigen reactivity.…”
Section: Combination Of Neoantigen Vaccine With Other Therapiesmentioning
confidence: 99%
“…Neoantigen-specific T cells can be identified in patients not only with melanoma, but also with epithelial cancers, such as lung cancer [119,120], gastrointestinal cancer [121][122][123], ovarian cancer [124][125][126], breast cancer [127] and pancreatic cancer [128]. Case reports have demonstrated that treatment of the gastrointestinal and breast cancer patients with a T cell population highly enriched in neoepitope-specific T cells caused tumour regression [121,123,127].…”
Section: Selection Of Neoantigen-specific T Cells From the Tumourmentioning
confidence: 99%
“…Combinatorial PD1 and CTLA4 blockade with adoptively transferred autologous PBMCs inhibit OVC growth in vivo in NSG mouse models We previously demonstrated that PBMCs and TILs/ TALs from OVC patients harbor tumor-recognizing T cells, and have efficacy toward autologous tumors. [25][26][27][28] We asked whether adoptive transfer of OVC patientderived autologous PBMCs or autologous TILs/TALs in combination with ICB can control OVC growth in NSG mice. The general scheme of tumor implantation, ACT, IL2 treatment and checkpoint blockade schedules are depicted in figure 4A.…”
Section: Clinical Characteristics and Immune Composition Of Tils/talsmentioning
confidence: 99%